2021
DOI: 10.1097/njh.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns of Pediatric Mental and Behavioral Health at End of Life

Abstract: Children, who enroll in hospice, have complex mental and behavioral health (MHBH) problems. There is limited literature on patterns of these problems among children at their end of life. Using the national database of 6195 children enrolled in hospice between January 1, 2011, and December 31, 2013, and latent class analysis, this study identified 4 distinctive classes of children. Neurodevelopment and anxiety class (26.5% of the sample) had 41.3% of children of 15 years or older, who had an average of 1.4 MHBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, limited research has examined the intersection of PPHC and mental illness and, in particular, the assessment and treatment of mental illness in pediatric patients who receive or who could benefit from both palliative and psychiatric care. [119][120][121] Further, as pediatric chronic illness management and palliative/hospice care shifts more heavily into the home setting and as treatment options become increasingly sophisticated, research that aims to understand patients', parents', home care nurses', and palliative and hospice providers' experiences of symptom assessment and management in the home is necessary. 79,86,122 Similarly, we must also improve symptom assessment and management for minoritized, historically marginalized communities.…”
Section: ✓ ✓ ✓mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, limited research has examined the intersection of PPHC and mental illness and, in particular, the assessment and treatment of mental illness in pediatric patients who receive or who could benefit from both palliative and psychiatric care. [119][120][121] Further, as pediatric chronic illness management and palliative/hospice care shifts more heavily into the home setting and as treatment options become increasingly sophisticated, research that aims to understand patients', parents', home care nurses', and palliative and hospice providers' experiences of symptom assessment and management in the home is necessary. 79,86,122 Similarly, we must also improve symptom assessment and management for minoritized, historically marginalized communities.…”
Section: ✓ ✓ ✓mentioning
confidence: 99%
“…Specifically, very little research on symptom assessment or management focuses on populations with developmental and/or neurologic characteristics that challenge usual assessment techniques, including younger children (neonates and 1- to 5-year-olds) and children with medically complex serious illnesses. In addition, limited research has examined the intersection of PPHC and mental illness and, in particular, the assessment and treatment of mental illness in pediatric patients who receive or who could benefit from both palliative and psychiatric care 119-121 . Further, as pediatric chronic illness management and palliative/hospice care shifts more heavily into the home setting and as treatment options become increasingly sophisticated, research that aims to understand patients', parents', home care nurses', and palliative and hospice providers' experiences of symptom assessment and management in the home is necessary 79,86,122 …”
Section: Priority Four: Pediatric Palliative and Hospice Research Pri...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings that mental and behavioral health was common among the "moderate intensity" and "high intensity" groups suggest that additional research is needed to better understand these health conditions at the end of life. Although there is emerging evidence about mental and behavioral health among children enrolling in hospice care, 35,36 we still do not know what specific mental and behavioral health services are needed and used. In addition, there is a gap in our knowledge about who is providing mental and behavioral health services and how those services are being coordinated during concurrent hospice care.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…5,6 Previous studies have also shown that concurrent hospice care may effectively reduce the costs of care. 2 Considering that children of different age groups require care of different intensity, [7][8][9] there is a need to assess the cost-effectiveness of concurrent care in reducing live discharges for children of different age groups.…”
mentioning
confidence: 99%